Plasmacytoid dendritic cells drive acute exacerbations of asthma - Chairakaki,A-D; Saridaki,M-I; Pyrillou,K; Mouratis,M-A; Koltsida,O; Walton,RP; Bartlett,NW; Stavropoulos,A; Boon,L; Rovina,N; Papadopoulos,NG; Johnston,SL; et al. (Journal of Allergy and Clinical Immunology, 2018)
BACKGROUND: Although acute exacerbations, mostly triggered by viruses, account for the majority of hospitalizations in asthma, there is still very little known about the pathophysiological mechanisms involved. Plasmacytoid DCs (pDCs), prominent cells of antiviral immunity, exhibit pro-inflammatory or tolerogenic functions depending on the context, yet their involvement in asthma exacerbations remains unexplored. OBJECTIVES: We sought to investigate the role of pDCs in allergic airway inflammation and acute exacerbations of asthma. METHODS: Animal models of allergic airway disease (AAD) and virus-induced AAD exacerbations were employed to dissect pDC function in vivo and unwind potential mechanisms involved. Sputum from asthma patients with stable disease or acute exacerbations was further studied to determine pDC presence and correlation with inflammation. RESULTS: pDCs were key mediators of the immuno-inflammatory cascade that drives asthma exacerbations. In animal models of AAD and RV-induced AAD exacerbations, pDCs were recruited to the lung during inflammation and migrated to the draining lymph nodes to boost Th2-mediated effector responses. Accordingly, pDC depletion post-allergen challenge or during RV infection abrogated exacerbation of inflammation and disease. Central to this process was IL-25, induced by allergen challenge or RV infection that conditioned pDCs for pro-inflammatory function. Consistently, in asthma patients pDCs were markedly increased during exacerbations, and correlated with the severity of inflammation and the risk for asthmatic attacks. CONCLUSIONS: Our studies uncover a previously unsuspected role of pDCs in asthma exacerbations with potential diagnostic and prognostic implications. They also propose the therapeutic targeting of pDCs and IL-25 for the treatment of acute asthma.